Moderasi Beragama dalam Pendidikan Islam - Hidayati, Hidayati (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2023)
This paper aims to answer the question of moderation in Islamic education, how the concept and implementation are. The research method used is a literature study approach with data analysis using meta-analysis. The results of the research analysis show that moderation in religion is an attitude and effort to make religion as a basis and principle to always avoid extremism (radicalism) and always look for a middle ground to unite all elements of society, nation, and state. While the indicators of moderation in religion consist of four indicators, namely: 1. National commitment 2. Tolerance 3. Anti-violence 4. Appreciation of local culture. Then in practice in Islamic education, moderation in religion must consider the following things: first, an interdisciplinary approach, second, the contextualization of Islamic messages. If moderation in religion is applied in madrasahs, it is very suitable because moderation (wasatiyyah) can be understood as a balance between strong beliefs and tolerance. Madrasahs are seen as one of the Islamic educational institutions that have relatively succeeded in instilling moderate Islam. Similarly, as pesantren as an Islamic educational institution begins to indicate the possibility of the emergence of radical ideas, then direct actualization can be carried out in the context of a multicultural society: First, making educational institutions as the basis of the laboratory of moderation in religion. Second, the approach of socio-religious moderation in religion and state. Keywords: Multicultural Society, Religious Moderation, Islamic Education Tulisan ini bertujuan untuk menjawab persoalan tentang moderasi beragama dalam Pendidikan Islam, bagaimanah konsep dan pelaksanaannya. Metode penelitian yang digunakan adalah pendekatan penelitian studi pustaka dengan analisis data menggunakan meta analisis. Hasil analisis penelitian menunjukkan bahwa moderasi beragama merupakan sikap serta upaya menjadikan agama sebagai dasar dan prinsip agar selalu menghindarkan diri dari sikap yang ekstrem (radikalisme) dan selalu mencari jalan tengah menyatukan semua elemen masyarakat, berbangsa, dan bernegara. Sedangkan indicator moderasi beragama terdiri dari empat indicator yakni: 1. Komitmen kebangsaan 2. Toleransi 3. Anti kekerasan 4. Peghargaan terhadap budaya lokal. Kemudian pada praktiknya dalam Pendidikan Islam, moderasi beragama harus mempertimbangkan hal-hal berikut ini: pertama, Pendekatan interdisipliner, kedua, kontekstualisasi pesan-pesan Islam. Jika moderasi beragama diterapkan di madrasah sangat cocok karena moderasi (wasatiyyah) dapat dipahami sebagai keseimbangan antara keyakinan yang kokoh dengan toleransi. Madrasah dipandang sebagai salah satu institusi pendidikan Islam yang relatif berhasil menanamkan Islam yang moderat. Sama halnya dengan Pesantren sebagai lembaga pendidikan Islam mulai terindikasi kemungkinan munculnya paham radikal, maka aktualisasi secara langsung dapat dilakukan dalam konteks masyarakat multikultural: Pertama, menjadikan lembaga pendidikan sebagai basis laboratorium moderasi beragama. Kedua, pendekatan moderasi sosio-religius dalam beragama dan bernegara. Kata kunci: Masyarakat Multikultural, Moderasi Beragama, Pendidikan Islam